HBsAg kinetics in chronic hepatitis D during interferon therapy: on‐treatment prediction of response. Issue 6 (22nd July 2016) - Niro, G. A.; Smedile, A.; Fontana, R.; Olivero, A.; Ciancio, A.; Valvano, M. R.; Pittaluga, F.; Coppola, N.; Wedemeyer, H.; Zachou, K.; Marrone, A.; Fasano, M.; et al.
Summary: Background: Therapy of chronic hepatitis D with Interferon is successful when testing for HDV‐RNA turns negative. This end‐point is disputed. Aim: To assess the role of serum hepatitis B surface antigen (HBsAg) in the clearance of HDV‐RNA in pegylated interferon (Peg‐IFN)‐treated chronic hepatitis D (CHD). Methods: Sixty‐two patients with CHD, treated with Peg‐IFN, were considered. The patients belonged to three groups: 14 patients cleared the HBsAg and HDV‐RNA (responders, R), 12 cleared the HDV‐RNA remaining positive for HBsAg (partial responders, PR) and 36 cleared neither the HBsAg nor the HDV‐RNA (nonresponders, NR). Results: In responders, at baseline the median value (mv) of HBsAg and HDV‐RNA was 1187 and 188 663 IU/mL. By month 6 of therapy, HBsAg declined to less than 1000 IU/mL and HDV‐RNA was undetectable in 12 patients. In NR, the pre‐therapy median value of HBsAg and HDV viremia was 6577 and 676 319 IU/mL. There was no significant reduction of antigen at month 6; after a decline, HDV‐RNA rebounded to baseline levels. In PR, the median value of baseline HBsAg was 7031 IU/mL; it declined at month 6 in the majority. HDV‐RNA progressively declined from an initial median value of 171 405 IU/mL. HBsAg <1000 IU/mL at month 6 discriminated responders and PR from NR ( P < 0.001). By ROC curve, the threshold of 0.105 log reduction of HBsAg associated with 1.610 log reduction of HDV‐RNA from baseline to month 6 predicted the clearance of this marker. Conclusions: A reduction of serum HBsAg is mandatory for the definitive clearance of the HDV‐RNA. Quantitative HBsAg may predict the long‐term response to Peg‐IFN therapy and provide a guide to prolong or stop treatment.